2022
DOI: 10.1371/journal.pone.0261702
|View full text |Cite
|
Sign up to set email alerts
|

Topology of synaptic connectivity constrains neuronal stimulus representation, predicting two complementary coding strategies

Abstract: In motor-related brain regions, movement intention has been successfully decoded from in-vivo spike train by isolating a lower-dimension manifold that the high-dimensional spiking activity is constrained to. The mechanism enforcing this constraint remains unclear, although it has been hypothesized to be implemented by the connectivity of the sampled neurons. We test this idea and explore the interactions between local synaptic connectivity and its ability to encode information in a lower dimensional manifold t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 42 publications
(49 reference statements)
0
22
0
Order By: Relevance
“…In particular, it is shown that an informed choice of neighbourhood improves classification accuracy when compared to traditional methods. Interestingly, the selection of neighbourhoods that improved performance with the technique presented in M. Reimann et al (2021) show reduced performance with the techniques presented in this article, and vice versa. In both projects a classification accuracy of nearly 90% was achievable, but with different selection parameters (see Results ).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In particular, it is shown that an informed choice of neighbourhood improves classification accuracy when compared to traditional methods. Interestingly, the selection of neighbourhoods that improved performance with the technique presented in M. Reimann et al (2021) show reduced performance with the techniques presented in this article, and vice versa. In both projects a classification accuracy of nearly 90% was achievable, but with different selection parameters (see Results ).…”
Section: Introductionmentioning
confidence: 75%
“…The primary test of our methods in this paper is done on data generated by the Blue Brain Project that was also used in M. Reimann et al (2021) for signal classification by established neuroscience methodology. The data consists of eight families of neuronal stimuli that are injected in a random sequence to the digital reconstruction of the neocortical column of a young rat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microcircuit also facilitates simulation of neuronal activity. Recently, various simulated activities were classified with high accuracy using feature vectors constructed from the network struc-ture [13,33]. The microcircuit is obtainable from [31].…”
Section: Data Descriptionmentioning
confidence: 99%
“…In topological data analysis (TDA) particularly the advent of applying topological tools to questions in neuroscience has spawned interest in constructing topological spaces out of digraphs, developing computational tools for obtaining topological information, and using these to understand networks and phenomena they support. For a progression of works on these ideas, see [13,29,32,33]. Our main example of a topological space on a digraph G is the directed flag complex, which is constructed from the directed cliques of G. For example, a 2-simplex is given by an ordered sequence of vertices (v 0 , v 1 , v 2 ) whenever any ordered pair (v i , v j ), for i < j, is a directed edge in G. By construction the simplices are endowed with an inherent directionality.…”
Section: Introductionmentioning
confidence: 99%